Declining Incidence of Rural Poverty in Kerala - K P Kannan (Economic and Political Weekly October 14-21, 1995, 1995)
In Kerala, the incidence of rural poverty has declined in the 1980s in spite of the slow rate of growth of the economy. The explanation for this is that various state intervention programmes, especially the public distribution system, have had a positive impact on poverty. The experience of Kerala shows that, with or without growth, it is possible to alleviate poverty through well designed and implemented programmes, and that social protection for the most vulnerable groups should be a necessary component of development policy.